Gender differentials among small scale irrigation farmers’ income: empirical evidence from cabbage farmers in KwaZulu-Natal, South Africa - Mkuna, Eliaza; Wale, Edilegnaw (Frontiers in Sustainable Food Systems, 2023)
Agricultural productivity and income disparities prevail between male and female farmers in Sub-Saharan Africa. South Africa is not an exception to this ominous reality. Using data from smallholder irrigation farmers in KwaZulu-Natal, South Africa, this study analysed the gender on-farm income gap by applying the Blinder-Oaxaca (OB) decomposition framework. The findings indicate that there is a significant difference in farm income between male and female farmers. Male farmers earn significantly higher on-farm income than female farmers by about R26,788/cropping season. The findings suggest that existing and future programs should focus on institutional factors (eg. land tenure) that affect access to resources and services. In addition to strategies to empower women, interventions to reduce the gender-induced farm income gap should focus on improving access to resources and services such as land with tenure security, agricultural input and output markets, training, information, and credit. Increasing the resource endowment and access to services by the female-managed farms is likely to significantly close the observed gender-induced farm income gap and improve the well-being of female farmers and their households.